Ocorrência de parasitos gastrintestinais em amostras fecais de felinos no município de Andradina, São Paulo - Coelho, Willian Marinho Dourado [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP]; de Soutello, Ricardo Velludo Gomes; Meireles, Marcelo Vasconcelos [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2009)
The purpose of this study was to verify the occurrence of gastrointestinal parasites in fecal samples from cats of the Andradina city, SP. This work was carried out from March to November of 2007, and used 51 cats delivered to the Center of Zoonoses Control of that city. Techniques of Willis and Faust were used in the fecal examination and resulted in detection of Ancylostoma spp. in 96.1% of the animals; Toxocara spp. in 43.1%; Cystoisospora spp. in 43.1%; Dipylidium caninum in 21.6% and Giardia spp. in 5.9% samples. Cryptosporidium spp. oocysts were detected in 3.9% fecal samples by the use of malachite green negative stain. There was no significant association between the occurrence of endoparasites and consistency of fecal samples. The results confirm that these cats represent important hosts of parasites, some of those with high zoonotic potential.
Occurrence of gastrointestinal parasites in fecal samples of cats in Andradina City, São Paulo
Keywords: Ancylostoma spp.; Cryptosporidium spp.; Giardia spp.; Public health; Toxocara spp.